Systemic Health Effects of Oleuropein and Hydroxytyrosol Supplementation: A Systematic Review of Randomized Controlled Trials - Oleg Frumuzachi; Laura Ioana Gavrilaș; Dan Cristian Vodnar; Sascha Rohn; Andrei Mocan (MDPI AG, 2024)
Non-communicable diseases (NCDs) cause 41 million deaths annually, accounting for 74% of global fatalities. The so-called Mediterranean diet, with its especially significant consumption of olive oil, has shown promising results in reducing the risk of developing NCDs, such as cardiovascular, liver, or bone diseases. In the context of the nutritional health benefits of foods, phenolic compounds such as olive oil's main components, oleuropein (OLE) and hydroxytyrosol (HT), have been shown to possess different beneficial effects. However, no systematic review has evaluated the health-promoting effects of OLE and HT until now. Consequently, this systematic review analyzed 12 human randomized controlled trials (RCTs), involving 683 participants, to assess the effects of supplements, pure compounds, or enriched foods containing OLE and HT regarding systemic health outcomes, including CVD risk factors, liver parameters, and bone, joint, and cognitive health. The review found contrasting but encouraging results, with some studies reporting significant modulation of body weight, lipid profile, and glucose metabolism, and improvements in bone, joint, and cognitive functions. The studies described different dosages and forms of supplementation, ranging from 5 mg/d HT to 990 mL/d olive leaf infusion (320.8 mg OLE and 11.9 mg HT), highlighting the need for further research to determine the optimal dosing and duration. Despite the mixed outcomes, OLE and HT supplementation show potential for improving some of the cardiometabolic health outcomes and bone, joint, and cognitive health. However, further studies are necessary to understand their benefits better and address existing limitations.